2019
DOI: 10.1097/cji.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related Adverse Events and Survival in Solid Tumors Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Immune-related adverse events (irAEs) are autoimmune-toxic effects associated with immune checkpoint inhibitors (ICIs) used for the treatment of advanced solid tumors. We performed a systematic review and meta-analysis of the published literature to assess the outcome for cancer patients treated with ICIs who develop irAEs. Two independent reviewers selected prospective or retrospective studies from PubMed, EMBASE, and the Cochrane Library database from their inception to November 2018. Data were pooled using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 60 publications
11
63
0
1
Order By: Relevance
“…26 As stated, several studies have described a significant association between irAEs and improved clinical outcomes with checkpoint inhibitors, even in patients with NSCLC. 1,2 However, to date, only 1 real world study, with a relatively small sample size, investigated this association in the setting of patients with NSCLC with PD-L1 expression ! 50% receiving first-line pembrolizumab, finding a significant association with improved PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 As stated, several studies have described a significant association between irAEs and improved clinical outcomes with checkpoint inhibitors, even in patients with NSCLC. 1,2 However, to date, only 1 real world study, with a relatively small sample size, investigated this association in the setting of patients with NSCLC with PD-L1 expression ! 50% receiving first-line pembrolizumab, finding a significant association with improved PFS.…”
Section: Discussionmentioning
confidence: 99%
“…The role of immune-related adverse events (irAEs) as a surrogate predictor of the efficacy of immune-checkpoint inhibitors has previously been described in a variety of malignancies. 1,2 Studies reported an association between the incidence of irAEs and improved outcomes, including among patients with nonesmall-cell lung-cancer (NSCLC) receiving programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors in different treatment lines. [3][4][5][6] Patients with metastatic NSCLC with a PD-L1 expression !…”
Section: Introductionmentioning
confidence: 99%
“…This process is defined as epitope spreading, which plays a crucial role in the initial stage of irAE development ( 62 ). Multiple studies demonstrated that the incidence of irAEs is significantly associated with the efficacy of ICIs ( 63 ), which can be partly explained by epitope spreading. Epitope spreading can also explain why different tumors treated with ICIs are associated with specific irAEs.…”
Section: Strategies To Prevent and Manage Iraes In Aid Patientsmentioning
confidence: 99%
“…This finding is compatible with suggestions of sustained responses of anti-PD-1 or anti-PD-L1 despite their suspension due to immune-related adverse effects. A meta-analysis shows an association between patient prognosis and the occurrence of immune-related adverse effects ( 19 ).…”
Section: Discussionmentioning
confidence: 99%